1987
DOI: 10.1067/mva.1987.avs0060583
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative predictors of mortality risk in ruptured abdominal aortic aneurysm

Abstract: A retrospective review of 106 cases of ruptured abdominal aortic aneurysm was undertaken to determine whether analysis of preoperative variables might be predictive of death in this condition. Thirty variables were analyzed by univariate and multivariate methods. Statistically significant differences between survivors and nonsurvivors were noted for 12 of 30 factors when analyzed with univariate tests. Multivariate analysis with stepwise logistic regression demonstrated that elevation of the unmeasured anion g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…As a result, most of the recent literature on ruptured AAAs has focused on selecting patients who are likely to survive, and some authors have advocated abandoning treatment for certain groups of patients who have risk factors that predict a poor outcome. 5,6,8,9,11,15,16,19,20,22 In addition, it has been thought that further improvement in surgical outcome is unlikely; therefore, the focus has shifted toward screening patients to treat aneurysms before they rupture. 3,8,12,18 -20 We believe the reason why the outcome after surgical repair of ruptured aortoiliac aneurysms (AIAs) has not improved relates to the fact that the basic surgical techniques for repairing ruptured AIAs remain little changed in the past four decades, although several improvements have been introduced.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, most of the recent literature on ruptured AAAs has focused on selecting patients who are likely to survive, and some authors have advocated abandoning treatment for certain groups of patients who have risk factors that predict a poor outcome. 5,6,8,9,11,15,16,19,20,22 In addition, it has been thought that further improvement in surgical outcome is unlikely; therefore, the focus has shifted toward screening patients to treat aneurysms before they rupture. 3,8,12,18 -20 We believe the reason why the outcome after surgical repair of ruptured aortoiliac aneurysms (AIAs) has not improved relates to the fact that the basic surgical techniques for repairing ruptured AIAs remain little changed in the past four decades, although several improvements have been introduced.…”
Section: Discussionmentioning
confidence: 99%
“…All patients with the diagnosis of abdominal aortic aneurysm who reached the operating theatre alive were studied. A literature search was performed and papers containing information on the survival of patients who had undergone abdominal aortic aneurysm repair were reviewed [1][2][3][4][5][6]. Factors which may be linked with prognosis were identified.…”
Section: Methodsmentioning
confidence: 99%
“…As these patients have poor physiological reserve, morbidity is high and survival poor. Reported mortality figures following emergency repair vary between 30 and 70% [1][2][3][4][5][6], while those for elective repair are lower at 1.4-6% [1,7,8]. Furthermore, abdominal aortic aneurysms are common, with an incidence of 17-64 per 100 000 of the population in the UK [9,10], and so emergency repair of abdominal aortic aneurysm represents a significant workload for vascular surgery and critical care services.…”
mentioning
confidence: 99%
“…In fact, as early as 1987, Shackleton et al (14) noted that an elevation of the unmeasured anion gap was significantly and independently associated with mortality for ruptured AAA patients. Grist and Thomas (28) reported that anion gap is a risk factor in long-term extracorporeal support.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high total mortality estimated at 80–100% for ruptured AA (8,9), the best way to reduce the overall mortality of the disease may be to detect and treat it prior to rupture. In fact, many predictors or predictive models of mortality risk in AA patients have been reported (1014), but further validation is required. Herein, we focused on AA patients in intensive care unit (ICU) and investigated the predictive value of serum anion gap on ICU mortality, a routine clinical indicator which has been reported to be associated with mortality of several diseases (1518).…”
Section: Introductionmentioning
confidence: 99%